PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Organizational culture is a pattern of behavior developed by an organization employees learni=ed when faced with problems of external adaption and internal integration, that has proven good enough to be approved and taught to new members as a way to realize, think and feel.